Molecular signal tracking and detection methods in fluid dynamic channels - Abbaszadeh, Mahmoud; Atthanayake, Iresha; Thomas, Peter J.; Guo, Weisi (IEEE, 2020)
This method and data paper sets out the macro-scale experimental techniques to acquire fluid dynamic knowledge to inform molecular communication performance and design. Fluid dynamic experiments capture latent features that allow the receiver to detect coherent signal structures and infer transmitted parameters for optimal decoding. This paper reviews two powerful fluid dynamical measurement methodologies that can be applied beneficially in the context of molecular signal tracking and detection techniques. The two methods reviewed are Particle Image Velocimetry (PIV) and Planar Laser-Induced Fluorescence (PLIF). Step-by-step procedures for these techniques are outlined as well as comparative evaluation in terms of performance accuracy and practical complexity is offered. The relevant data is available on IEEE DataPort to help in better understanding of these methods
Keywords: PLIF; PIV; fluid dynamics; macro-scale; experimentation; molecular communication